THE EFFECT OF ENVIRONMENTAL MANAGEMENT ACCOUNTING ON FIRM VALUE - Bahtiar Effendi (Bajang Institute, 2021)
This research study aims to examine the effect of implementing environmental management accounting in increasing firm value in Tangerang Raya. This research uses a population of 2,579 manufacturing industrial companies in Banten province spread across Cilegon City, Serang Regency and City, Pandeglang City, Lebak City and Tangerang Raya. The samples were selected using predetermined criteria with quantitative methods. Based on the multiple linear regression testing that has been carried out, the following results are obtained: there is a significant positive effect between the material input aspect and the environmental complaint mechanism aspect on firm value. Furthermore, the results of non-output aspects of products and aspects of compliance have a significant negative effect on firm value. However, there are three aspects of the proxy for the application of environmental management accounting which consist of transportation aspects, other aspects, and supplier assessment aspects that have a positive and insignificant effect on firm value. Simultaneously, the effect of the application of environmental management accounting proxied through material input, environmental complaint mechanism, non-product output, compliance, transportation, supplier assessment and others have a significant effect on firm value.